A computational study of the effects of polycrystalline structure on residual stress-strain concentrations and fracture in metal-matrix composites. (August 2022) - Balokhonov, R.; Romanova, V.; Zinovieva, O.; Dymnich, E.
Highlights: Deformation and fracture of Al6061T6-ZrC composite are numerically studied. 3D FEM microstructure of polycrystalline matrix with particle of irregular shape is created. Combined isotropic-anisotropic elastic–plastic-brittle constitutive models are developed. Polycrystalline structure is shown to prevent fast through-the-thickness cracking of composites. Abstract: Deformation and fracture of metal-matrix composites are numerically investigated. Composite microstructures with a single ceramic particle in a homogeneous or polycrystalline matrix are generated by the step-by-step packing method. The thermoelastic-plastic reaction of the matrices is described using isotropic and anisotropic relations, including the associated plastic flow rule and crystal plasticity theory. The thermoelastic response of a ceramic particle is isotropic. In order to describe the crack initiation and propagation in the matrix and particle, two fracture criteria with the limiting values of the equivalent plastic strain and stress are developed. During cooling both pure shear and volumetric tension stress regions are formed in the matrix around the particle. The polycrystalline structure of the matrix prevents through-the-thickness crack formation during subsequent mechanical loading of the composite. Grain boundaries cause multiple stress concentrations and plastic strain localizations all over the matrix material, which delays fracture near the matrix-particle interface.